PENGARUH BAURAN PEMASARAN TERHADAP TINGKAT PENJUALAN DI CV. IRWAN SHOP - Vitri Handayani; Prihartono Prihartono (Eqien - Jurnal Ekonomi dan Bisnis, 2022)
This study aimed to determine the extent of the influence of marketing mix on sales rate. This study uses quantitative methods and data collection methods using the questionnaire method. The subjects in this research are consumers in CV. Irwan Shop. The object of this research is the marketing mix and sales rate in CV. Irwan Shop. The population in this study were consumers of CV. Irwan shop, consisting of 132 consumers who have been netted for 2 months, with a sample of 30 respondents. Data collection techniques are interviews, observation, documentation, and a list of questions. Data analysis used descriptive analysis, validity and reliability, correlation coefficient analysis, coefficient of determination, multiple correlation and linear regression. The hypothesis test used is the T test (partial test) and the F test (simultaneous test). From the results of data analysis, it was found that the partial product was positive and had a significant effect on product sales rate in CV. Irwan Shop. Product is the most dominant variable affecting sales rate. Price has a positive and significant effect partially on product sales rate in CV. Irwan Shop. Some promotions are positive and have a significant effect on product sales rate in CV. Irwan Shop. Place partially has a positive and significant effect on product sales rate in CV. Irwan Shop. Simultaneously product, price, promotion, and place have a significant effect on product sales rate in CV. Irwan Shop. Doing business in an online shop needs to maintain product quality, price conformity, innovation in promoting and all placed in an effort to boost sales rate.